The Implementation of Contra Legem Principle in Dividing Joint Assets Post Divorce for Different Contributions Maqasid Shari’ah Perspective - Rohimah, Na'imatur; Jamilah, Jamilah (Sakina: Journal of Family Studies, 2024)
The dividing of joint assets after divorce plays a central role in the achievement of justice. This research explores the case of the dividing of joint assets at the Malang Regency Religious Court; the defendant opposed the claim for joint assets with the argument that the joint assets were realized more by the wife because her father assisted it. This study aims to analyze the judge's consideration in deciding the dividing of joint assets by using the contra legem principle in case number 1786/Pdt.G/2023/PA.Kab.Mlg and its analysis in maqsid shar’ah. This research is empirical research using a descriptive qualitative approach; this research was conducted at the Religious Court of Malang Regency using interview and documentation methods. The results showed that 1). The dividing of joint assets by 70% for the counterclaim defendant and 30% for the counterclaim plaintiff is based on distributive justice that looks at the legal facts in the trial. 2). The maqsid shar’ah analysis confirms that the decision supports the preservation of assets, offspring, and soul in the context of the basic needs of the darriyt. In addition, it provides convenience for both parties without having to start from scratch in the context of hajiyt needs.